The natural history of tassel-eared squirrels - Allred, Sylvester, 1946- (University of New Mexico Press, 2010)
"I live in the middle of an almost two-million-acre ponderosa pine forest--the largest in the world. In moments I can leave my home and be in the habitat of the tassel-eared squirrel, which I have studied for more than twenty-five years. From my dining table I can watch these tassel-eared rascals climb along a branch of a ponderosa pine, clip terminal pine shoots for inner bark, gather pollen cones for their rich golden pine pollen, and consume the seeds from developing ovulate cones. Any of us in Flagstaff, Arizona, or Boulder, Colorado, or Santa Fe, New Mexico, who live in houses placed in the habitat of these squirrels have the opportunity to see these animals whose relationship with the ponderosa pine forest is so unique, since with rare exception these animals live only in ponderosa habitat. Tassel-eared squirrels can bring both endless entertainment and numerous frustrations to homeowners. Some encourage them by placing foods out for them to eat, and others desperately try to keep these one and one-half-pound acrobats from raiding their bird feeders. --.